Magneto-structural Coupling Field Analysis on the End Winding of a Multi-phase Induction Machine - Huang Tao; Ruan Jiangjun; Zhang Yujiao; Hu Yuanchao; Sun Mengyun; Liu Hailong (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In order to study the steady-state electromagnetic forces acting on the stator end-winding in a multi-phase induction machine during the operation, we conducted a 3-D electromagnetic and mechanical sequential coupling analysis to analyze the stress and the deformation. Both of them are done by the finite-element method. Meanwhile, the geometry of the nose portion is modified for the limited computer resources. The result shows the nose part of the coil ends experiences larger displacement, but von Mises stresses are larger in the straight part. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1283